2013
DOI: 10.1111/dote.12043
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the number of occult metastatic lymph nodes on postoperative relapse of resectable esophageal cancer

Abstract: Clinical stage II/III esophageal cancer (EC), as defined by the Japanese Classification, relapses at a moderately high rate even after curative resection. The number of lymph node metastases is known to be associated with tumor relapse. Recently, the prognostic significance of occult metastatic lymph nodes (MLNs), as well as that of overt MLNs, has been reported. The aim of this study was to investigate the impact of the total number of MLNs including occult MLNs on postoperative relapse in clinical stage II/I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
1
3
1
2
Order By: Relevance
“…These patients presented with a total of 137 (5.0%) lymph node micrometastases. Other studies found 8.0% to 38.0% pN0 esophageal cancer patients with a micrometastatic lymph node involvement and micrometastases in 1.0% to 49.0% of the investigated lymph nodes [8,[25][26][27][28][29]. Hence, our data are within the reported range of the literature.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These patients presented with a total of 137 (5.0%) lymph node micrometastases. Other studies found 8.0% to 38.0% pN0 esophageal cancer patients with a micrometastatic lymph node involvement and micrometastases in 1.0% to 49.0% of the investigated lymph nodes [8,[25][26][27][28][29]. Hence, our data are within the reported range of the literature.…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, the prognostic implications of LNMM and BNMM are still being debated. The majority of studies have also found a reduced overall or disease-free survival in LNMM positive patients [8,9,25,28,29]. Heeren et al investigated 60 initially pN0 staged cancers of the gastroesophageal junction reporting a reduced disease-free survival in patients with a micrometastatic nodal involvement [8].…”
Section: Discussionmentioning
confidence: 99%
“…Whether an extensive lymph node dissection could improve the 5-year OS rates is still under debate (10). Some studies indicate that extensive lymph node dissection could improve prognosis (24)(25)(26), but other studies state that it is not associated with better survival (11,27). In our study, patients with more than 15 resected lymph nodes did not show a survival advantage compared with patients with less than 15 resected lymph nodes.…”
contrasting
confidence: 51%
“…Whether patients with esophageal cancer will benefit from more lymph node dissection is still debated. Although data from some studies (13)(14)(15)(16) and our own center (17) agreed that the number of lymph nodes removed during esophagectomy was significantly associated with prognosis, some other studies indicate that extensive lymph node dissection is not associated with better prognosis (18,19). Furthermore, even for authors advocating for more lymph node dissections, the best cut-off remains unclear, with the recommended thresholds varying from 12 to 30 (20,21).…”
Section: Lymph Node Dissection and Survivalmentioning
confidence: 91%